New water-soluble cationic indium (III) phthalocyanine bearing thioquinoline moiety; Synthesis, photophysical and photochemical studies with high singlet oxygen yield - Kutlu, Oznur Dulger; Avcil, Dilan; Erdogmus, Ali (IOS PRESS, 2019)
The synthesis and characterization of (4) -tetra[2-thioquinoline] phthalocyaninato indium (III) (2) and quaternized (4)-tetra[2-thioquinoline] phthalocyaninato indium (III) (3), are described. Photochemical and photophysical properties of 2 and 3 in DMSO; and of 3 in water are also presented. A comparison between the photophysical and photochemical parameters of 2 and 3 showed that 2 is a better photosensitizer than 3. The quantum yield values of fluorescence (Phi(F)), and singlet oxygen formation (Phi(Delta)) for 2 are 0.012 and 0.74, respectively. These values are higher than those for 3, which exhibited the values 0.006 and 0.66, respectively. The values for 3 in aqueous solution are 0.002 and 0.17 (0.42 plus Triton X-100) respectively due to aggregation behavior in the solution, and these values suggest that indium phthalocyanine 2 and its water-soluble derivative 3 can find use as photosensitizer in the photodynamic therapy (PDT) of cancer.
Keywords: Indium (III) phthalocyanine; photochemistry; singlet oxygen; photophysics; SUBSTITUTED GALLIUM; QUANTUM YIELDS; PHOTOSENSITIZERS; QUINOLINES; TETRA; ZINC; AGGREGATION; Chemistry